An analysis of goal scored that differentiate between winning and losing team in the knockout stage of the UEFA EURO Championship 2016 / Anuarul Amir Ramli - Ramli, Anuarul Amir (Faculty of Sport Science and Recreation, 2017)
This study was conducted in order to analyze goal scored that differentiate between winning and losing team in the knockout stage of UEFA EURO championship 2016. 15 match starts from round 16 to final match were selected to be observed. The indictor include for this analysis were the goal scoring area, goal scoring time, type of shot used to score goal and the position of the scorer. Mann Whitney test used to see the significant of this study. For goal scoring area, the highest frequency of goal scoring is at low left area between winning (Mean ± SD), (0.80 ± 0.676) and losing (0.07 ± 0.258), (Z = -3.350, p<0.05). The mean rank of winning team is higher than losing team with (20.07 vs. 10.94). The second indicator is goal scoring time, the highest frequency of goal scoring time is at 31-45 minutes between winning (Mean ± SD), (0.53 ± 0.640) and losing (0.00 ± 0.000), (Z =-2.958, p< 0.05). For the Mean rank the winning team show the higher result compare to the losing team (19.00 vs. 12.00). Thirdly type of shot used to score goal, the highest frequency of type of shot used to score a goal is header between winning (Mean ± SD), (0.53 ± 0.743) and losing (0.07 ± 0.258), (Z = -2.163, p<0.05). The results of Mean rank of winning team have higher compare to losing teams (18.07 vs. 12.93). Moreover, the highest frequency of pitch area where the ball was score is at the middle area between winning (Mean ± SD), (1.67 ± 0.976) and losing (0.47 ± 0.640), (Z = -3.407, p<0.05). Mean rank show that the winning team have higher results compare losing team (20.07 vs. 10.30). Lastly, the highest frequency of position of the scorer is at inside box area between winning (Mean ± SD), (1.73 ± 1.100) and losing (0.40 ± 0.632), (Z = - 3.379, p<0.05). The results for mean rank show that, winning team have higher mean compare to losing team (20.67 vs. 10.33).